Validation of Impacts of Widely Acknowledged Human Factors in Risk Management of Residential Construction Projects - Salma, Shaik; Santha Rao, P (International Journal of Engineering and Technology, 2018)
In the countries like India where one has to still handle a unique blend of operational diversities like human operated traditional construction practices and modern construction technologies, in all construction projects that are highly vulnerable to socio-economic, political, technical and business risks. The involvement of the people with diverse educational, technical, economical and experience backgrounds is an unavoidable fact of the construction industry in India and hence the human factors are going to play a key role in the project to be more prone to risks as well as to mitigate the likely projects risks. Due to lack of robust risk management system, many prestigious construction projects in India have suffered failures and have impacted the country’s GDP and growth because of the gigantic share of the construction industry in the country’s economy. Hence, the risk management in the construction industry has become the subject of concern for the industry practitioners and so the analysis of operational difficulties for the identification and management of construction related risks to minimize the cost overruns, quality deviations and uncertain delays, is remained to be the main objective of the research by the domain experts and engineers for so long. In this paper, an attempt has been made to review all such papers with a specific aim to identify and analyze the human factors that, are highly acknowledged by experts in their works and, can influence / impact the project parameters namely cost, time and quality and validate the results by tracking a real time construction project to draw conclusions.